Faktor-faktor yang Memengaruhi Persepsi Umat Kristen terhadap Islam Terkait Tindakan Terorisme - Mark Phillips Eliasaputra; Tonni Hutabarat; Anam Prayer Manurung; Alvin Koswanto (Sekolah Tinggi Teologi Ekumene Jakarta., 2022)
Acts of terrorism are often associated with Islam; even though Islam itself teaches its adherents as a religion of sowing love for the whole world. But in reality, the terrorists justify their actions by reason of jihad or holy war. This can lead to negative perceptions among people of other religions towards Islam, so that it can interfere with inter-religious harmony. This study aims to determine whether there is a negative perception among Christians towards Islam regarding acts of terrorism and what factors influence it. This explanatory research uses a cross-sectional approach. In collecting data, researchers used a questionnaire or questionnaire. Data analysis was performed using the Stepwise multiple linear regression test. From the research that has been done, the results show that even though there are acts of terrorism, the majority of Christians still have a positive perspective on Islam. Negative perceptions of Christians regarding terrorism are influenced by negative attitudes from external parties towards Islam and a lack of knowledge about Islam.